PENYEBAB PERDARAHAN IBU POSTPARTUM - Purwanti, Dwi; Ratnasari, Febi; Winarni, Lastri Mei (Nusantara Hasana Journal, 2022)
A total of 830 maternal deaths occur every day. The main complication that causes almost 75% of all maternal deaths, one of which is severe postpartum hemorrhage. Objective to review articles that discuss the causes of postpartum maternal bleeding. The author uses a literature review. In searching for several articles, this literature uses the Google Scholar, Pubmed and e-Resources databases with inclusion criteria, namely using Indonesian and English, respondents are mothers who experience postpartum hemorrhage, articles obtained from primary sources and the time span of the article is 5 years (2017-2021). Based on the literature review, it was found that the causes of postpartum hemorrhage were uterine atony, birth canal tears, retained placenta and placental rest are direct causes of postpartum hemorrhage, as well as type of delivery, age, parity, gestational distance, anemia, bleeding history, oxytocin drip, labor induction, family income, education and work are indirect factors of postpartum hemorrhage.